Modulation of BiOBr-based photocatalysts for energy and environmental application: A critical review. Issue 2 (April 2022) - Zhao, Guo-Qing; Hu, Jun; Zou, Jiao; Long, Xuan; Jiao, Fei-Peng
Abstract: To get rid of this dilemma of global energy crunch and environmental pollution problem, up to now, semiconductor photocatalytic technology, using solar energy as the driving force, has been considered as one promising strategy to solve energy and environmental problems. As for the semiconductor-based photocatalysts, BiOBr has obtained wide attention because of its unique narrowed bandgaps, low cost, nontoxicity as well as higher structure stability. Moreover, many results have demonstrated that BiOBr-based photocatalysts exhibit remarkable photocatalytic activity in the fields of energy catalytic conversion and environmental remediation. In view of these, the critical review summarized the structure information, design and synthesis strategy as well as the photocatalytic applications (such as photodegradation of organic pollutions, photocatalytic hydrogen generation, reduction of CO2 to some valued chemicals and so on.) of BiOBr-based materials. Finally, a concise perspective about current challenge and prospects of BiOBr are discussed. Overall, this full-scale review is wished to provide some references to reasoningly design high active BiOBr-based photocatalysts for environment remediation and green solar-fuel generation. Graphical Abstract: ga1 Highlights: Recent development of BiOBr-based composites for energy and environmental applications was comprehensively summarized. The synthesis methods for BiOBr-based composites were reviewed. Various approaches for the enhanced photocatalytic performance of BiOBr-based materials were comprehensive summarized. The key issues and possible future research directions have made some corresponding outlooks in the following research.